Determinant of Land Use Change in South Kalimantan: An Evidence from Banjarbaru City and Banjar Regency - Supriatna Supriatna; Fathia Hashilah; Mutia Kamalia Mukhtar; Kartika Kusuma Wardani (Forestry Faculty, Universitas Hasanuddin, 2022)
Environmental degradation, biodiversity loss, climate change, and other environmental catastrophe are negative impacts caused by irresponsible land use change. It is vital to investigate the driver of the land use change to avoid undesirable environmental catastrophes. On the other hand, determinants of the occurrence of the land use change are very complex to be identified. In the last few years, floods hit many parts of the world, one of them was a massive flood in South Kalimantan in the last few years. There is a presumption that this disaster is caused by land use changes inside the watershed. This paper aims to identify the determinants of the land use change in Banjarbaru City and Banjar Regency inside Martapura and Maluka Watershed. This study found out that having a secure land tenure per se does not incentivize landowners to prevent land use change. However, having a secure land tenure is a crucial factor in affecting land use change if the land they own is in large size. Having secure land tenure with large land size affects the occurrence of land use changes significantly by conducting agricultural and plantation extensification. This situation depicts that agricultural and plantation extensification exists in the rural area of South Kalimantan, which is triggered by economic profit orientation. Thus, the accumulation of secure land tenure and large land size need to be considered as land use change determinants for current and future’s land use policy in the context of Indonesia.